The perception of non-Muslim tourists towards halal tourism - Battour, Mohamed; Hakimian, Fatemeh; Ismail, Mohd Nazari; Boğan, Erhan (Emerald, 2018)
Purpose: This paper aims to explore the perceptions of non-Muslim tourists towards halal tourism in Malaysia and Turkey. It also investigates the extent to which non-Muslim tourists are willing to purchase certain types of halal products and services. Design/methodology/approach: Qualitative data were collected by conducting 35 semi-structured interviews with non-Muslim tourists in Malaysia and another 25 in Turkey. Findings: Six major aspects are identified that describe the perceptions of non-Muslim tourists towards halal tourism. This paper also provides some suggestions for destination marketers on how best to cater for Western tourists and increase international arrivals. Originality/value: This paper explores the perceptions of non-Muslim tourists towards halal tourism which is totally new research in destination marketing. It provides some original insights into the interactions between the religion of Islam and non-Muslim tourists. The insight should be of value to authorities, the industry and academics in both the Muslim and non-Muslim worlds.